PENGUASAAN KETERAMPILAN KONSELING GURU PEMBIMBING DI YOGYAKARTA - Rosita Endang Kusmaryani (Jurnal Kependidikan, 2010)
The purpose of this multi-year study is to identify the mastery of counseling skills of guidance teachers in Yogyakarta. A proportional sample of 33 junior high, senior high and vocational school guidance teachers in Yogyakarta participate in the study as research subjects. The research data are collected using a questionnaire instrument of counseling skills mastery and analyzed by quantitative and qualitative descriptive techniques. The results show that: 1) There are some counseling skills that are often used, but have not been mastered well. Some of these skills of counseling are attending, asking questions, giving support, clarifying, problem solving, focusing, and giving encouragement. 2) Most of the guidance teachers have not used these skills optimally in the counseling process. The suggestion of this study is to improve the mastery of the guidance teachers counseling skills through training, either through role playing or through practicing directly in handling cases. Teaching materials such as modules that assess counseling skills are needed. In addition, the schools need to provide support for guidance teachers to develop their performance by following the training to improve their mastery of counseling skills